Development and content validation of the Muscular Dystrophy Child Health Index of Life with Disabilities questionnaire for children with Duchenne muscular dystrophy. (29th July 2018) - Propp, Roni; McAdam, Laura; Davis, Aileen M; Salbach, Nancy M; Weir, Shannon; Encisa, Clarissa; Narayanan, Unni G
Abstract : Aim: To develop a patient‐reported outcome measure that comprehensively captures the health‐related priorities of children with Duchenne muscular dystrophy (DMD). Method: Children with DMD and their parents completed the iteratively revised versions of the Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD), followed by a cognitive interview to develop a pilot version of a new measure. Multidisciplinary health care professionals completed an item‐by‐item analysis of the measure and a 14‐item sensibility questionnaire. Minimum content validity ratio for each item of the new measure and the mean score (0–7) for the items of the sensibility questionnaire were calculated. Results: The CPCHILD underwent changes over 19 interviews with children and their parents, resulting in the pilot Muscular Dystrophy Child Health Index of Life with Disabilities (MDCHILD). The content validity ratio of each MDCHILD item ranged from 0.85 to 1 based on health care professionals' ratings. The mean score exceeded the threshold of four for all items of the sensibility questionnaire. Based on child, parent, and health care professional recommendations, 16 items were added, six eliminated, and 15 items modified from the original CPCHILD. The MDCHILD consists of 47 items over seven domains. Interpretation: The MDCHILD met all sensibility criteria by children with DMD, their parents, and health care professionals, and is ready for psychometric evaluation. What this paper adds: The Muscular Dystrophy Child Health Index of Life with Disabilities (MDCHILD) is a new patient‐reported outcome measure for Duchenne muscular dystrophy (DMD). The Priority Framework of Outcomes underpins the content for the MDCHILD. The MDCHILD incorporates the health‐related priorities of males with DMD and their parents. The MDCHILD was deemed sensible by children, their parents, and health care professionals. What this paper adds: The Muscular Dystrophy Child Health Index of Life with Disabilities (MDCHILD) is a new patient‐reported outcome measure for Duchenne muscular dystrophy (DMD). The Priority Framework of Outcomes underpins the content for the MDCHILD. The MDCHILD incorporates the health‐related priorities of males with DMD and their parents. The MDCHILD was deemed sensible by children, their parents, and health care professionals. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.